PENGGUNAAN METODE COURSE REVIEW HORAY DENGAN MEDIA GRAFIS DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS V SDN BANYUURIP TAHUN AJARAN 2014/2015 - Nur Fadila, Isnaini (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Use of Course Review Horay Method with Graphic Media in Improving Social Science Learning for the Fifth Grade Students of SDN Banyuurip in the Academic Year of 2014/2015. The purposes of this research was improving social science learning for the fifth grade students of elementary school using Course Review Horay method with graphic media. This research was collaborative classroom action research. It was conducted in three cycles consisting of planning, action, observation, and reflection on each cycle. Subjects of this research were students in the fifth grade of SDN Banyuurip, consisting of 18 students. Source of data were obtained from students, teachers, colleagues, researchers and documents. The techniques of collecting data were test, observation, interview, and documentation. This research results show that of Course Review Horay method with graphic media can improving social science learning on the fifth grade students of SDN Banyuurip in The academic Year of 2014/2015.Keywords: Course Review Horay, graphic media, Social Science learningAbstrak: Penggunaan Metode Course Review Horay dengan Media Grafis dalam Peningkatan Pembelajaran IPS Siswa Kelas V SDN Banyuurip Tahun Ajaran 2014/2015. Penelitian ini bertujuan untuk meningkatkan pembelajaran IPS siswa kelas V SD menggunakan metode Course Review Horay dengan media grafis. Penelitian ini merupakan penelitian tindakan kelas kolaboratif. Penelitian dilaksanakan dalam tiga siklus terdiri dari perencanaan, pelaksanaan, pengamatan, dan refleksi. Subjek penelitian ini adalah siswa kelas V SDN Banyuurip berjumlah 18 siswa. Data berasal dari siswa, guru, teman sejawat, peneliti, dan dokumen. Teknik pengumpulan data menggunakan tes, observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa metode Course Review Horay dengan media grafis dapat meningkatkan pembelajaran IPS siswa kelas V SDN Banyuurip tahun ajaran 2014/2015.Kata Kunci: Course Review Horay, media grafis, pembelajaran IPS